2012
DOI: 10.4149/neo_2012_047
|View full text |Cite
|
Sign up to set email alerts
|

Cellular stress response in Eca-109 cells inhibits apoptosis during early exposure to isorhamnetin

Abstract: The flavonol aglycone isorhamnetin shows anti-proliferative activity in a variety of cancer cells. Previous work, from our laboratory showed that isorhamnetin inhibits the proliferation of human esophageal squamous carcinoma Eca-109 cells in vitro, but only after 72 h of exposure. This led us to propose that isorhamnetin exposure induces a cellular stress response that inhibits the antiproliferative and apoptotic effects of the compound during early exposure. To test this hypothesis, the present study examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…[12,26,27] Interestingly, a study of esophageal squamous carcinoma reported that the NF-κB pathway showed activation in the first 72 h exposure of IH but became inhibited later. Explanation of this phenomenon was that cellular stress response (involving NF-κB activation) inhibited cell apoptosis in the early exposure [10]. However, cell apoptosis dominated later, leading to NF-κB inhibition.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,26,27] Interestingly, a study of esophageal squamous carcinoma reported that the NF-κB pathway showed activation in the first 72 h exposure of IH but became inhibited later. Explanation of this phenomenon was that cellular stress response (involving NF-κB activation) inhibited cell apoptosis in the early exposure [10]. However, cell apoptosis dominated later, leading to NF-κB inhibition.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…[6,7] Isorhamnetin shows a variety of pharmacological activities such as cardiovascular protection, antioxidant, anticholinesterase, and antibacterial. [8,9] Besides, its anticancer effect has been proven in esophageal cancer [10], colon cancer [11], breast cancer [12], and lung cancer [13]. However, to the best of our knowledge, there is no research focusing on the inhibitory effect of IH in melanoma, and the mechanism underlying has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…1), a 3 0 -O-methylated metabolite of quercetin, is one of the naturally distributed flavonoids and has been confirmed that it can dilate coronary artery, protect cardiomocytes against oxidation, and has effects of antitumor and hemostasis functions. [1][2][3] Cardiovascular diseases are a leading cause of mortality around the world, and ischemia/reperfusion (I/R) injury plays a major role in cardiovascular diseases such as myocardial infarction. 4,5 Previous studies have demonstrated that IsoRN could prevent apoptosis of cardiomyocytes caused by anoxia/reoxygenation (A/R), an in vitro I/R model.…”
Section: Introductionmentioning
confidence: 99%
“…These two herbs are administered for the treatment of rheumatism, hemorrhage and cancer in traditional medicine ( 20 22 ). Isorhamnetin is the active compound of these herbal medicinal plants, and is an immediate metabolite of quercetin, also termed 3′-O-methylquercetin, which has been shown to inhibit various types of cancer, including esophageal ( 23 ) and gastric cancer ( 24 ), leukemia ( 25 , 26 ), skin ( 27 ), colon ( 28 ) and lung cancer ( 29 ). However, to the best of our knowledge, no study to date has focused on the inhibitory effects of isorhamnetin on breast cancer, and the molecular mechanisms underlying its effects remain unclear.…”
Section: Introductionmentioning
confidence: 99%